Magnetic properties of the ternary FeCoxNi1−x alloy: Monte Carlo simulations. Issue 17 (2nd September 2022) - Saber, N.; Fadil, Z.; Mhirech, A.; Kabouchi, B.; Bahmad, L.; Ousi Benomar, W.
ABSTRACT: The paper studies the magnetic properties of the ternary FeCox Ni1–x alloy with mixed spins Fe(S = 2), Co(σ = 3/2) and Ni(q = 1), using Monte Carlo simulations under the Metropolis Algorithm. Firstly, we explore the ground state phase diagrams in order to identify all possible and stable configurations based on the minimisation of the system energy in different physical parameters planes. In addition, the magnetisations and the magnetic susceptibilities as a function of the temperature have been studied. Moreover, the effects of the crystal field, the exchange coupling parameters on the magnetizations and the hysteresis loops have been investigated for different values of the concentration ratio x of the Co atoms. It is found that the ratio x affects strongly the magnetisation, the susceptibility, the transition temperature and the hysteresis loops of the studied system.